(2-(4-Bromophenyl)ethene-1, 1, 2-triyl)tribenzene with aggregation induced emission for ablation of HeLa cells. (16th August 2018) - Yang, Jie; Gu, Xiaoqing; Su, Wanting; Hao, Xinyu; Shi, Yujie; Zhao, Liyun; Zou, Dengfeng; Yang, Gaowen; Li, Qiaoyun; Zou, Jianhua
Abstract : TPE-Br with aggregation induced emission can inhibit the growth of HeLa cells both in vitro and in vivo . Abstract : It is of great importance for a photosensitizer to be soluble in aqueous solutions, while simultaneously remaining highly fluorescent. Towards this goal, (2-(4-bromophenyl)ethene-1, 1, 2-triyl)tribenzene (denoted asTPE-Br ) with aggregation induced emission (AIE) was prepared. 1, 2-Distearoyl- sn-glycero -3-phospho-ethanolamine- N -[methoxy(polyethyleneglycol)-2000 ] (DSPE-PEG-2000 ) coatedTPE-Br nanoparticles (NPs) have a strong ability to generate singlet oxygen using singlet oxygen sensor green (SOSG) as a probe and still retain high fluorescence in aqueous solutions. In vitro cytotoxicity assays demonstrate that these NPs are able to kill HeLa cells effectively and the half-maximal inhibitory concentration (IC50 ) is as low as 12 μg mL −1 . Furthermore, in vivo investigation suggests thatTPE-Br NPs are able to inhibit the growth of the tumors after irradiation without adverse effects to normal organs, including the heart, liver, spleen, lung and kidney. This indicates the significantly low dark toxicity and excellent biocompatibility of such NPs.